Association of daily physical activity and bone microarchitecture in young adults with type 1 diabetes — A pilot exploratory study - Sarah L. West; Michelle Furman; Rahim Moineddin; Etienne Sochett (Bone Reports)
Purpose: Physical activity (PA) is an important determinant of skeletal health. In young adults with type 1 diabetes (T1D) fracture risk is increased, yet few studies have examined the PA and bone health relationship. Therefore, this pilot cross-sectional study characterized PA levels and their association with bone parameters measured by high resolution peripheral quantitative computed tomography (HR-pQCT) in young adults with T1D. Methods: HR-pQCT (Xtreme CTII) was used to measure bone outcomes at the distal tibia and radius, and accelerometery (ActiGraph GT3X) recorded daily minutes of light and moderate-vigorous physical activity (MVPA). Quadratic regression analyses were conducted with a p-value ≤ 0.05 considered significant. Results: PA data from 19 young adults (23.1 ± 1.9 years) with T1D was analyzed. Over half (63 %) of participants completed ≥150 min of MVPA per week, however, most measured activity time per day (57 %) was spent in sedentary pursuits. Significant non-linear associations were found between the duration of MVPA and several trabecular bone parameters at the tibia. Conclusions: In young adults with T1D, MVPA may have site specific (tibia) and compartment specific (trabecular) non-linear associations with bone. Further studies should confirm these findings, which may help inform evidence-based exercise recommendations to optimize bone health in young adults with T1D.